A checklist of Iranian Grasses - Bidarlord, Mahmoud; Ghahremaninejad, Farrokh (Phytotaxa, 2022)
This paper provides a taxonomic treatment for the large angiosperm family, the Poaceae, in Iran. The last comprehensive review of Iranian Grasses (Poaceae) dates back to half a century ago in Flora Iranica. Since then, a number of taxa have been described as new species or newly recorded from Iran, and some names have been placed in synonym. This study presents a comprehensive and updated account of all reported Iranian grasses and their classification. The results include 128 genera, 477 species, 64 subspecies and 44 varieties belonging to 37 subtribes, 19 tribes, and seven subfamilies, of which 28 taxa are endemic for Iran. The genera, Elymus, with 7 species and Festuca, with 5 species have the highest number of endemic species. The most diverse genera in Iran are, Bromus (39 spp.), Festuca (27 spp.), Stipa (27 spp.), and Poa (26 spp.). Poeae is the largest tribe, and Pooideae is the largest subfamily in Iran. This paper provides a new name, Festuca neopersica a new combination, Leymus europaeus as well as nomenclatural modifications on the basis of recent taxonomic and molecular investigation of Poaceae taxa related to Iran. The comparison of the species distribution in Iran with that in neighboring countries indicates that Turkey has the most and the Arabian Peninsula the least species in common with Iran, with 305 (64%) and 156 (32%) species, respectively. The species shared with Iran, Pakistan and Saudi Arabia are placed mainly in PACMAD clade, while the species shared with Iran, Turkey and Transcaucasia are mainly placed in PEB clade. Grasslands in Iran are in need of more protection as a result of climatic change and human actions.